Penerapan Metode MOOSRA dalam Rekomendasi Platform Investasi Emas Online Terbaik dengan Pembobotan ROC - Hanifah Ekawati; Yunita Yunita (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
In the current era, technology is considered more practical in doing all kinds of things, for example, making investments that initially could only be done in person and were considered complicated, but now with technology, investments can be made online, making it more practical. Investments can be made by the younger generation, not only by their parents, the younger generation needs to learn about various things about investing with the aim of preparing for a brighter future. Investments that can be made by the younger generation can be in various forms, one of which is gold investment. Gold investment can be done by buying physical gold such as jewelry or gold bars, or by means of non-physical gold investment such as through the futures market, gold mutual funds, or online gold investment platforms. The online gold investment platform offers competitive gold prices and gold storage services in a secure warehouse to make it easier for investors to buy and sell gold online. However, because there are so many gold investment platforms, young gold investors are confused about determining the best online gold investment platform to use. The application of a decision support system is used in this study to solve problems in the recommendation of the best gold investment platform by applying the MOOSRA (Multi-Objective Optimization on the Basis of Simple Analysis) method and ROC (Rank Order Centroid) weighting. Then several criteria are used in the recommendations for the best gold investment platforms, namely Rating Reviews, Integrated E-commerce, Number of Payment Methods, Number of Partners and Minimum Purchases. By applying the MOOSRA and ROC methods, the best gold investment platform results with the highest preference value are obtained in alternative P2, namely BukaEmas with a value of 1151.88524.